Living arrangements and lonely life expectancy: a multistate life table based on Markov chains - Qi Yu; Jilei Wu (Population Health Metrics)
Abstract Background The evolution of family structures in China has led to changes in the living arrangements of older adults, resulting in an increasing prevalence of individuals living alone. This shift has raised concerns about the impact on the well-being of older adults, particularly in relation to loneliness. The objective of this study is to examine the association between living alone and lonely life expectancy (LLE) among older adults, with particular attention to gender differences. Methods This study analyzed data from 9664 individuals aged 65–105, drawn from the Chinese Longitudinal Healthy Longevity Survey (CLHLS) conducted in 2008, 2011, 2014, and 2018. A multistate life table approach, coupled with interpolation Markov Chain methods using IMaCh software (version 0.99r43), was employed to estimate age-specific transition probabilities, life expectancy (LE), lonely life expectancy (LLE), and the proportion of LLE to LE (LLE/LE). The analysis was stratified by gender and living arrangements, distinguishing between individuals living alone and those not living alone. Results The study identified several key findings. First, while LE has increased among older adults in China, they continue to experience a substantial duration of LLE. Second, older adults living alone experienced both longer LLE and higher LLE/LE ratios. Specifically, the LLE/LE among individuals not living alone was 13.61% higher for males and 15.18% higher for females compared to those living alone. Third, among females living alone, the LLE/LE was the highest, reaching 39.48% at age 65, compared to just 20.96% for males not living alone. Conclusions Tackling persistent loneliness is essential for enhancing the quality of life among older adults, highlighting the need to integrate mental well-being into social welfare policies. As China's population ages and family structures continue to evolve, living arrangements emerge as crucial policy indicators. Prioritizing the mental health of older adults, particularly women living alone, is critical for the development of effective social security policies.